2010
DOI: 10.1016/j.neuroimage.2009.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social comparison on the neural substrates of reward processing: An event-related potential study

Abstract: Event-related potentials (ERPs) were recorded to explore the electrophysiological correlates of reward processing in the social comparison context when subjects performed a simple number estimation task that entailed monetary rewards for correct answers. Three social comparison stimulus categories (three relative reward levels/self reward related to the other subject's) were mainly prepared: Self:Other=1:2 (Disadvantageous inequity condition); Self:Other=1:1 (Equity condition); and Self:Other=2:1 (Advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 42 publications
4
44
4
Order By: Relevance
“…A study using electroencephalographic (EEG) recordings identified event-related brain potential (ERP) correlates with this social comparison effect. Both disadvantageous and advantageous unequal payoff elicited a larger late negative component (LNC), between 550 and 750 ms, when compared to equal payoff conditions (Qiu et al, 2010). Source analysis revealed that the generators of the LNC were localized near the caudate nucleus.…”
Section: Introductionmentioning
confidence: 89%
“…A study using electroencephalographic (EEG) recordings identified event-related brain potential (ERP) correlates with this social comparison effect. Both disadvantageous and advantageous unequal payoff elicited a larger late negative component (LNC), between 550 and 750 ms, when compared to equal payoff conditions (Qiu et al, 2010). Source analysis revealed that the generators of the LNC were localized near the caudate nucleus.…”
Section: Introductionmentioning
confidence: 89%
“…Boksem et al . 39 found enhanced FRN when participants’ own outcomes were worse than those of others, but neither Wu et al 40 nor Qiu et al 41 replicated these results. What seemed to matter in these two other experiments was not so much whether the participant received a higher payoff than the other player, but rather whether the two players were equitably rewarded.…”
Section: Brain Response To Objective and Relative Outcomesmentioning
confidence: 95%
“…The impact of such counterfactual choices is even more pronounced in social settings, indicating that these may provide additional information for learning (Coricelli and Rustichini, 2010). One ERP study indicates that the FRN to one's own outcomes might be modulated as a function of whether a co-player wins or loses at the same time (Qiu et al, 2010). In an fMRI study on social comparison, dACC activation was related to envying others' success, whereas schadenfreude was associated with ventral striatum activity when gloating over the misfortune of a previously envied person (Takahashi et al, 2009).…”
Section: Social Influences On the Monitoring Of Self-generated Actionsmentioning
confidence: 99%